MT forward modeling of 3-D anisotropie electrical conductivity structures using the rayleigh-fourier method - Martinelli, P. (1997)
We present an algorithm for modeling the magnetotelluric response of three-dimensional multilayered structures with irregular interfaces. In this formulation, based on a RayleighFourier technique, the effect of vertical anisotropy in the electrical conductivity has also been included. This method has an applicability range complementary to other solutions based on finite differences or on integral equations, which are especially adequate to model localized bodies intruded in a host medium. To test the method, the MT response of a simple conductive structure was modeled and compared with the solutions obtained using integral equations. A good agreement between the results with similar processing times have been observed. Finally, the effect of anisotropy was estimated for the particular case of a conductive basin, showing a non-negligible contribution, depending on the relation between the vertical and horizontal values of the conductivity.